2020
DOI: 10.1111/aas.13568
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic use of acid suppressants in adult acutely ill hospitalised patients: A systematic review with meta‐analysis and trial sequential analysis

Abstract: Background Acutely ill patients are at risk of stress‐related gastrointestinal (GI) bleeding and prophylactic acid suppressants are frequently used. In this systematic review, we assessed the effects of stress ulcer prophylaxis (SUP) with proton pump inhibitors (PPIs) or histamine‐2 receptor antagonists (H2RAs) versus placebo or no prophylaxis in acutely ill hospitalised patients. Methods We conducted the review according to the PRISMA statement, the Cochrane Handbook and GRADE, using conventional meta‐analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 81 publications
1
18
0
Order By: Relevance
“…They suggested that the increased incidence of pneumonia caused by PPIs was due to confounders, and proton pump itself was not an independent factor affecting the occurrence of pneumonia. [13][14][15][16] According to our study, the PPIs use had no relation with the duration of the SARS-CoV-2 clearance and the hospital stay. We preferred the opinion that the PPIs use did not increase the probability of pneumonia.…”
Section: Key Ndingsmentioning
confidence: 55%
See 1 more Smart Citation
“…They suggested that the increased incidence of pneumonia caused by PPIs was due to confounders, and proton pump itself was not an independent factor affecting the occurrence of pneumonia. [13][14][15][16] According to our study, the PPIs use had no relation with the duration of the SARS-CoV-2 clearance and the hospital stay. We preferred the opinion that the PPIs use did not increase the probability of pneumonia.…”
Section: Key Ndingsmentioning
confidence: 55%
“…They believed that the increased incidence of pneumonia caused by PPIs was due to confounding factors, and PPIs itself was not an independents factor affecting the occurrence of pneumonia. [13][14][15][16] In addition, studies have shown that PPIs can effectively inhibit virus and can be tried to treat viral infection and respiratory disease. [17][18] It is not clear whether PPIs will have a signi cant impact on COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the increased incidence of pneumonia caused by PPIs was due to confounders, and proton pump itself was not an independent factor affecting the occurrence of pneumonia. [13][14][15][16] According to our study, the PPIs use has no relation with the duration of SARS-CoV-2 clearance and hospital stay by Cox regression and the propensity score method. We prefer the opinion that the PPIs use does not increase the probability of pneumonia.…”
Section: Discussionmentioning
confidence: 67%
“…They believed that the increased incidence of pneumonia caused by PPIs was due to confounding factors, and PPIs itself was not an independents factor affecting the occurrence of pneumonia. [13][14][15][16] Basic studies have shown that PPIs can effectively inhibit virus-specific serine proteases and thus play an antiviral role. [17] And H+/K+-ATPase inhibitors can be tried to treat viral infection and respiratory disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation